Utility of p63 and AMACR in Differentiating Benign and Malignant Prostatic Lesions - Koshy, Ashily; Bavikar, Rupali (Annals of Pathology and Laboratory Medicine, 2021)
Background: Prostate cancer is the sixth most common cancer in the world. Since treatment options and prognosis of prostatic adenocarcinomas and benign lesions differ significantly, so, the current study using p63and AMACR was carried out with aim to evaluate the utility of immunohistochemistry in resolving ambiguous lesions of prostate. Methods: The study was conducted on 130 prostatic specimens which included prostate biopsy, TURP and prostatectomy specimens. Routine hematoxylin and eosin staining and immunohistochemical staining using AMACR, p63 monoclonal antibody marker were performed. Results: Total of 130 cases of prostate samples were studied out of which benign lesions were seen in 102 cases (78.5%) and malignant carcinoma in 28 cases (21.5%). This study showed p63 had a sensitivity of 92.86% and specificity of 100% whereas AMACR has a sensitivity of 96.4% and specificity of 95%. BPH with prostatitis was a common finding in majority of benign lesions. All cases of LGPIN 15 cases (11.5%) were histologically associated with BPH, showing complete positivity in 12 cases (80%) and partial positivity in 3 cases (20%) with p63 immunostaining. HGPIN (1.5%) were associated with prostatic adenocarcinoma showing focal positivity whereas adenocarcinoma showed complete negativity of p63 expression (100%) and positive cytoplasmic staining with AMACR. Comparative study done between DRE, PSA, final histopathological diagnosis, expression of p63 and AMACR immunostaining gives highly significant p value of 0.001(<0.05). Conclusion: p63 and AMACR are reliable markers which can be used in morphologically difficult cases.